Depression, Recurrence, and Perceptions of Physical Fitness among CHD Patients: A Comparison based on Participation in Phase II Cardiac Rehabilitation Program - Aan Nuraeni; Atlastieka Praptiwi; Ikeu Nurhidayah (Jurnal Keperawatan Padjadjaran, 2020)
Coronary heart disease (CHD) patients experience various physical and psychological changes after an acute attack. Depression has been identified as a substantive psychological problem in CHD patients. Cardiac rehabilitation (CR) intends to restore optimal physical and psychological condition of the patients. However, less attention is bestowed towards the psychological aspect of CR. Research on the effects of CR on patient psychological problems has not been discussed in many studies in Indonesia. This study aimed to compare depression, recurrence, and fitness levels among CHD patients based on participation in Phase II CR Program. This research used a quantitative comparative method involving 66 CHD patients recruited by a purposive sampling technique. After applying the selection criteria for this study, the patients were assigned to the CR group (nCR=29) and the non-CR group (nNCR=37). Data were collected using the Beck Depression Inventory-II (BDI II) and instruments developed by researchers to measure recurrence and fitness levels. Data were analyzed using frequency distribution, chi-squared, and Mann-Whitney tests. Depression experienced by CHD patients in both groups with mean in non-CR and CR groups of 11.11 (± 7.8) and 8.59 (± 6.5), respectively. There was no significant difference in depression level among the groups (p>0.05)). Meanwhile, as many as 45% of the patients in the CR group and 22% in the non-CR group had never experienced chest pain (recurrence) within the past month. In addition, the physical fitness was perceived increased by 90% of the patients in the CR group and 0% in the non-CR group. It was also found that there were significant differences in the recurrence and physical fitness among the two groups (p <0.05). Patients participating in Phase II CR program had a better perception of physical fitness and a lower frequency of chest pain than patients in the non-CR group. Although the depression level in patients in the two groups did not differ significantly, patients in the non-CR group scored higher in depression. Accordingly, assessment and psychosocial interventions need to be improved to optimize CR program services.